IUTAM Symposium on Computational Physics and New Perspectives in Turbulence Proceedings of the IUTAM Symposium on Computational Physics and New Perspectives in Turbulence, Nagoya University, Nagoya, Japan, September, 11-14, 2006 - Kaneda, Yukio; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
This volume contains the proceedings of the IUTAM Symposium on Computational Physics and New Perspectives in Turbulence, held at Nagoya University, Nagoya, Japan, in September 2006. Leading experts in turbulence research were brought together at this Symposium to exchange ideas and discuss, in the light of the recent progress in computational methods, new perspectives in our understanding of turbulence. Special emphasis was given to fundamental aspects of the physics of turbulence. The subjects discussed here cover: computational physics and the theory of canonical turbulent flows; experimental approaches to fundamental problems in turbulence; turbulence modeling and numerical methods; and geophysical and astrophysical turbulence. This work should be useful to graduate students and researchers interested in fundamental aspects of turbulence.
Computational Physics and Theory for Canonical Turbulence -- Some Contributions and Challenges of Computational Turbulence Research -- Global Scaling Properties of Heat and Momentum Transport in Fluid Flow -- Linear and Angular Momentum Invariants in Homogeneous Turbulence -- Energy Dissipation and Pressure in 4d Turbulence -- On Intermittency in Shell Models and in Turbulent Flows -- Enstropy Generation and Regularity of Solutions to the 3D Navier-Stokes Equations -- Attempts at Computer-Aided Understanding of Turbulence -- Effect of Large-Scale Structures upon Near-Wall Turbulence -- Multifractal Analysis by Using High-Resolution Direct Numerical Simulation of Turbulence -- Fine Scale Eddy Cluster and Energy Cascade in Homogeneous Isotropic Turbulence -- Acceleration Statistics of Inertial Particles from High Resolution DNS Turbulence -- Heavy Particle Clustering in Turbulent Flows -- Reynolds Number Effects on the Turbulent Mixing of Passive Scalars -- Statistical Theory of Turbulence Based on Cross-Independence Closure Hypothesis -- Multi-Scale Analysis of Turbulence -- Helicity within the Kolmogorov Phenomenology of Turbulence -- Anomalous Scaling Laws of Passive Scalar Intermittency in 3-Dimensional Turbulence -- Multifractal PDF Analysis of Energy Dissipation Rates in Turbulence -- Scale Interactions and Non-Local Flux in Hydrodynamic Turbulence -- Control over Multiscale Mixing in Broadband-Forced Turbulence -- Coherent Structures in Marginally Turbulent Square Duct Flow -- Extraction of Multi-Scale Vortical Structures from a Homogeneous Isotropic Turbulence -- Orthonormal Divergence-Free Wavelet Analysis of Nonlinear Energy Transfer in Rolling-Up Vortices -- Wavelet-Based Statistics of Energy Transfer in High Reynolds Number Three-Dimensional Homogeneous Isotropic Turbulence -- Experimental Approach to Fundamental Problems in Turbulence -- Visualization of Quantized Vortex Dynamics -- Lagrangian Measurements of Fluid and Inertial Particles in Decaying Grid Generated Turbulence -- Shear Effect on Pressure and Particle Acceleration in High-Reynolds-Number Turbulence -- On the Development of Wall-Bounded Turbulent Flows -- Scaling Law of the Near Wall Flow Subjected to an Adverse Pressure Gradient -- Non-Equilibrium and Equilibrium Boundary Layers without Pressure Gradient -- Experimental Study of Laminar Turbulent Boundary Layer Transition Influenced by Anisotropic Free Stream Turbulence -- Statistical Features of Scalar Flux in a High-Schmidt-Number Turbulent Jet -- Large Scale Structure in Turbulent Plane Couette Flow -- Vortex Tubes in Turbulence Velocity Fields at High Reynolds Numbers -- Wavelet Analysis of Vortex Breakdown -- Turbulence Modeling and Numerical Methods -- Renormalized Numerical Simulation of Flow over Planar and 3D Fractal Trees -- Wavelet-Based Extraction of Coherent Vortices from High Reynolds Number Homogeneous Isotropic Turbulence -- Decaying 2D Turbulence in Bounded Domains: Influence of the Geometry -- New One- and Two-Point Scaling Laws in Zero Pressure Gradient Turbulent Boundary Layer Flow -- Intrinsic Langevin Models for Turbulence -- Analysis of the Reynolds Stress Using the Green's Function -- On Turbulence Characteristics Around the Two-Dimensional Symmetric Aerofoil: Kinematic Simulation and Experiments -- Eddy Viscosity in Magnetohydrodynamic Turbulence -- Large Eddy Simulation of a Turbulent Boundary Layer Flow over Urban-Like Roughness -- A Spectral Method for Unbounded Domains and Its Application to Wave Equations in Geophysical Fluid Dynamics -- A Model for the Far-Field Anisotropic Acoustic Emission of Rotating Turbulence -- Geophysical, Astrophysical and Complex Turbulence -- Dynamics of the Small Scales in Magnetohydrodynamic Turbulence -- Recent Experimental and Computational Studies Related to the Fluid Dynamics of Clouds -- Strongly Anisotropic Turbulence Using Statistical Theory: Still a Computationally Demanding Problem -- Vortical Interactions with Interfacial Shear Layers -- Magnetostrophic Turbulence and the Geodynamo -- MHD Turbulence: Nonlocal, Anisotropic, Nonuniversal? -- Structure Formation in Stratified Turbulence -- Reduced Models for Rotating and Stratified Flows -- Three-Dimensional Stability of Vortices in a Stratified Fluid -- Simulation of Strongly Stratified Fluids -- Numerical Simulation of Quantum Fluid Turbulence -- Turbulent Drag Reduction by Wall Deformation Synchronized with Flow Acceleration -- On the Large Scale Evolution of Rotating Turbulence -- Effects of the Slow Modes in the Differential Diffusion in Stratified Sheared Turbulence -- Numerical Study of 3-D Free Convection under Rotation: Mean Wind and Bolgiano-Obukhov Scaling -- The Horizontal Energy Spectra and Cascade Processes in Rotating Stratified Turbulence -- Parameter Dependence of Eastward-Westward Asymmetric Jets in Forced Barotropic 2D Turbulence on a ?-plane -- Statistics of Quasi-Geostrophic Vortex Patches -- The Breakdown of a Columnar Vortex with Axial Flow -- Evolution of an Elliptical Flow in Weakly Nonlinear Regime.
Keywords: ENGINEERING; COMPUTER SCIENCE -- MATHEMATICS; HYDRAULIC ENGINEERING; ENGINEERING; ENGINEERING FLUID DYNAMICS; FLUID- AND AERODYNAMICS; STATISTICAL PHYSICS, DYNAMICAL SYSTEMS AND COMPLEXITY; COMPUTATIONAL MATHEMATICS AND NUMERICAL ANALYSIS; NUMERICAL AND COMPUTATIONAL PHYSICS